More Profitable Rice Varieties Crowd Beneficial Landraces Out - Pathak, Krishna Prasad (Journal of Agriculture and Environment, 2010)
The study compares gross revenues from modern rice varieties and landraces and valuates different useful traits of rice landraces to demonstrate an empirical methodology for biodiversity valuation. A sample of 200 rice growers in hills and plain area was surveyed for commercialization of agro-biodiversity project. For estimating the value put by the consumers on different rice traits a hedonic pricing model was used that disaggregates the prices paid by the consumers for different useful traits of rice. The results show that the consumers value aromatic and tasty traits much higher than other traits. As the farmers are earning much lower income from many landraces as compared to that from modern varieties, the farmers are likely to replace them by the modern varieties. The findings of the study will be helpful to prepare market based strategies for rice biodiversity conservation, particularly for the conservation of rice landraces. Key words: Agrobiodiversity; Biodiversity-valuation; Hedonic-pricing; Rice-landrace; Traits The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 1-9 Uploaded Date: 15 September, 2010